Compromise, optimal and tractional accounts on Pareto set - Lahuta, V. V. (Science and Transport Progress, 2011)
The problem of optimum traction calculations is considered as a problem about optimum distribution of a resource. The dynamic programming solution is based on a step-by-step calculation of set of points of Pareto-optimum values of a criterion function (energy expenses) and a resource (time).